Rare Cause of Recurrent Hypoglycemia: Insulin Autoimmune Syndrome - Tinmanee, Rungsima (Case Rep Endocrinol, 2017)
We report a case of insulin autoimmune syndrome associated with several autoantibodies, presenting with recurrent hypoglycemia, predominantly in the postprandial period, which improved by dietary management and spontaneously resolved within two months. Differentiation from other causes of hyperinsulinemic hypoglycemia, such as insulinoma, is important to avoid unnecessary invasive procedures or surgical interventions. The 75-gram oral glucose tolerance test (OGTT) and mixed meal test showed a typical pattern, which may be useful indirect evidence of insulin autoimmune syndrome.